ChemInform Abstract: Organocatalytic Enantioselective Construction of Polyaromatic Architectures. Issue 51 (23rd December 2014) - Quinonero, Ophelie; Bressy, Cyril; Bugaut, Xavier
Abstract Review: 17 refs.